Expectations of the size evolution of massive galaxies at 3 ≤ z ≤ 6 from the TNG50 simulation: the CEERS/JWST view - Costantin, Luca; Pérez-González, Pablo G.; Vega-Ferrero, Jesús; Huertas-Company, Marc; Bisigello, Laura; Buitrago, Fernando; Bagley, Micaela B.; Cleri, Nikko J.; Cooper, Michael C.; Finkelstein, Steven L.; Holwerda, Benne W.; Kartaltepe, Jeyhan S.; et al. (The astrophysical journal, 2023)
We present a catalog of about 25,000 images of massive (M ⋆ ≥ 109 M ⊙) galaxies at redshifts 3 ≤ z ≤ 6 from the TNG50 cosmological simulation, tailored for observations at multiple wavelengths carried out with JWST. The synthetic images were created with the SKIRT radiative transfer code, including the effects of dust attenuation and scattering. The noiseless images were processed with the mirage simulator to mimic the Near Infrared Camera (NIRCam) observational strategy (e.g., noise, dithering pattern, etc.) of the Cosmic Evolution Early Release Science (CEERS) survey. In this paper, we analyse the predictions of the TNG50 simulation for the size evolution of galaxies at 3 ≤ z ≤ 6 and the expectations for CEERS to probe that evolution. In particular, we investigate how sizes depend on the wavelength, redshift, mass, and angular resolution of the images. We find that the effective radius accurately describes the three-dimensional half-mass-radius of the TNG50 galaxies. Sizes observed at 2 μm are consistent with those measured at 3.56 μm at all redshifts and masses. At all masses, the population of higher-z galaxies is more compact than their lower-z counterparts. However, the intrinsic sizes are smaller than the mock observed sizes for the most massive galaxies, especially at z ≲ 4. This discrepancy between the mass and light distributions may point to a transition in the galaxy morphology at z = 4-5, where massive compact systems start to develop more extended stellar structures. 22
Gesehen am 26.06.2023